Дослідження верхньопалеолітичної стоянки Озерове на Кіровоградщині - Залізняк, Л.Л.; Вєтров, Д.О.; Манько, В.О.; Хоптинець, І.М.; Озеров, П.І. (Археологічні дослідження в Україні, 2009)
The paper is devoted to the publication of the material from the research in 2008 of a new Upper Palaeolithic settlement Ozerove in the basin of the Velyka Vys River.